2021
DOI: 10.3390/ijms22168530
|View full text |Cite
|
Sign up to set email alerts
|

Roles of CCL2-CCR2 Axis in the Tumor Microenvironment

Abstract: Chemokines are a small family of cytokines that were first discovered as chemotactic factors in leukocytes during inflammation, and reports on the relationship between chemokines and cancer progression have recently been increasing. The CCL2-CCR2 axis is one of the major chemokine signaling pathways, and has various functions in tumor progression, such as increasing tumor cell proliferation and invasiveness, and creating a tumor microenvironment through increased angiogenesis and recruitment of immunosuppressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 122 publications
(158 reference statements)
2
61
0
Order By: Relevance
“…The results of migration assay experiments would confirm the anti-metastatic effects of vitamin D on thyroid cancer cell lines. However, the fact that basal cell migration occurred in a dose-dependent manner and was observed also for concentrations of vitamin D at which no inhibitory effect on chemokine secretion was demonstrated would support that the anti-migration effect of vitamin D would depend upon other mechanisms rather than by its ability to inhibit the secretion of CCL2 and CXCL8, chemokines that are known to be crucially involved in the metastatic process ( 27 , 32 34 ).…”
Section: Discussionmentioning
confidence: 94%
“…The results of migration assay experiments would confirm the anti-metastatic effects of vitamin D on thyroid cancer cell lines. However, the fact that basal cell migration occurred in a dose-dependent manner and was observed also for concentrations of vitamin D at which no inhibitory effect on chemokine secretion was demonstrated would support that the anti-migration effect of vitamin D would depend upon other mechanisms rather than by its ability to inhibit the secretion of CCL2 and CXCL8, chemokines that are known to be crucially involved in the metastatic process ( 27 , 32 34 ).…”
Section: Discussionmentioning
confidence: 94%
“…A recent study found the increase of CCL2 promoted carcinogenesis through esophageal mucosal inflammation [ 13 ]. Moreover, CCL2 could promote the survival and proliferation of THP-1, prostate cancer cell line PC3, renal cell carcinoma cell line 786-O and KAKI-1, and lung cancer cell line A549 [ 14 , 15 ]. The growth of cutaneous squamous cell carcinoma and non-small-cell lung cancer was promoted by tumor-cell-derived complement components C1r and C1s [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, various stromal cells in the TME, including endothelial cells, DCs, fibroblasts, and adipocytes, are capable of producing CCL2 to promote tumor growth and progression. 90 , 91 , 92 CCL2 was the first CC chemokine to be identified and fully studied and has a high affinity for its receptor, CCR2. It has been revealed that CCR2 is widely expressed in a broad range of cell types, including monocytes, 93 endothelial cells, 94 DCs, 95 and various cancer cells and the upregulation of CCR2 is related to advanced cancer, metastasis, and relapse.…”
Section: Different Chemokine Axesmentioning
confidence: 99%
“… 96 After reaching a new organ and/or tissue, residual circulating tumor cells are able to successfully colonize and continue to grow through interactions with various components within the TME. 91 It has been suggested that CCL2 might act as an autocrine or paracrine chemokine to promote the growth of tumor cells, which can be partially abolished by CCR2 antagonists or PI3K inhibitors. 115 CCL2 can promote drug resistance in gastric cancer cells by inhibiting autophagy, and either knockdown of CCL2 or induction of autophagy successfully reversed drug resistance in tumor cells.…”
Section: Different Chemokine Axesmentioning
confidence: 99%